Epidemiological study of viral diseases in fish and shrimp at hatchery and grow-out phases in Malaysia - Daud, H. M.; Samson, N. G.; Wang, Y. G.; Al-Sahtout, A. H. (Universiti Putra Malaysia Press, 2004)
A study was undertaken to determine the presence and incidence of viral disease infection in cultured fish (carps, catfishes, tilapias) and shellfish (tiger shrimp, Penaeus monodon ) in Malaysia. Samples were obtained from farm visits and clinical cases submitted. Fish and shrimps samples were processed accordingly by routine laboratory culture and microscopic studies and examined for the presence of infectious agents. A new variant of Cyprinid herpesvirus (CHV) was detected in koi carp (Cyprinus carpio) with papillomatous skin growth, while in shrimp important diseases viz., WSSD, YHD, MBV, IHHNV, BMN and HPV were detected.